Feeding Turkey Poults with Starter Feed and Whole Wheat or Maize in Free Choice Feeding System: Its Effects on Their Performances - Erener, G.; Ocak, N.; Garipoǧlu, A.V.; Şahin, A.; Öztürk, E. (Asian-Australasian Association of Animal Production Societies, 2006)
This study was carried out to determine the effects of free choice feeding of starter feed and whole cereals on the growth of turkey poults. Two hundred-seventy poults (7-d old) were divided into 3 treatment groups each with 3 replications containing 15 males and 15 females. Control poults (C) were fed only on starter feed (280 g CP and 11.7 MJ ME/kg). Treatments for choice-fed turkey poults were offered a choice of a starter feed and wheat (120 g CP and 12.3 MJ ME/kg) for wheat selecting (WS) or maize (83 g CP and 13.9 MJ ME/kg) for maize selecting (MS) group in separate feeders. Final live weight (2,280.7 g for the C vs. 2,374.3 and 2,324.6 g for the WS and MS), daily gain (39.21 g vs. 40.87 and 39.99 g) and total feed intake (95.2 g vs. 103.2 and 97.9 g) in the WS poults were significantly higher (p<0.05) than those of the C group, but feed conversion ratio was not significantly different between the treatments. The proportional intakes of cereals vs. total feed intake were 11% in both the WS and MS group. The amount of protein intake in the C group (280 g CP/kg diet) was significantly (p<0.05) higher than that in WS and MS groups (263 and 259 g CP/kg diet, respectively) whilst the ME intake in the C group (11.7 MJ/kg diet) was significantly (p<0.05) lower than that in MS group (11.9 MJ/kg diet). Our results showed that turkey poults fed starter feed and whole wheat in a free choice feeding system have a higher efficiency in terms of daily gain, final live weight, and an economic advantage may be obtained from free choice feeding due to a reduced protein intake and feed cost.
Keywords: Choice Feeding; Growth Performance; Turkey Poults; Whole Cereals